Magnetoimpedance exchange coupling in different magnetic strength thin layers electrodeposited on Co-based magnetic ribbons - Jamilpanah, L; Hajiali, MR; Mohseni, SM; Erfanifam, S; Mohseni, SM; Houshiar, M; Roozmeh, SE (IOP Publishing, 2017)
A systematic study of the effect of the deposition of cobalt (Co) and nickel (Ni) layers of various thicknesses on the magnetoimpedance (MI) response of a soft ferromagnetic amorphous ribbon (Co68.15Fe4.35Si12.5B15) is performed. The Co and Ni layers with thicknesses of 5, 10, 20 and 40 nm were grown on both sides of the amorphous ribbons by the electrodeposition technique. Microstrutures determined by x-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM) showed higher crystallinity of Ni-deposited layers and the amorphous ferromagnetic nature of Co-deposited. The vibrating sample magnetometry (VSM) does not represent significant changes between samples because of the small contribution of such a thin layer deposited on thick ribbons, but the MI response dictates that the magnetic coupling effect occurred at the interface of such bilayers, which is sensitive to the skin effect. The MI response of Co-deposited ribbons showed MI hysteretic behavior depending on the deposited layer thicknesses with an optimum response for the thickness of 20 nm whereas no hysteretic behavior was measured for Ni-deposited ribbons. This behavior is explained according to the exchange coupling between magnetization of electrodeposited layers and magnetic ribbons with respect to different magnetic properties of Co and Ni at different thicknesses. Also the MI response of Ni- and Co-deposited ribbons enhanced significantly at low thicknesses relative to bare ribbon. By increasing the thickness of deposited layers, MI response decreases considerably. Differences in MI ratios of Co- and Ni-deposited ribbons are explained according to exchange length, crystallinity and roughness of deposited layers. Our results could address a simple way to achieve a higher MI response, and explains physical aspects of exchange coupling in MI response all towards a better performance of magnetic field sensors.